Natural Products based P-glycoprotein Activators for Improved β-amyloid Clearance in Alzheimer’s Disease: An in silico Approach - Shinde, Pravin; Vidyasagar, Nikhil; Dhulap, Sivakami; Dhulap, Abhijeet; Hirwani, Raj (Central Nervous System Agents in Medicinal Chemistry, 2016)
Alzheimer’s disease is an age related disorder and is defined to be progressive, irreversible neurodegenerative disease. The potential targets which are associated with the Alzheimer’s disease are cholinesterases, N-methyl-D-aspartate receptor, Beta secretase 1, Pregnane X receptor (PXR) and P-glycoprotein (Pgp). P-glycoprotein is a member of the ATP binding cassette (ABC) transporter family, which is an important integral of the blood-brain, blood-cerebrospinal fluid and the blood–testis barrier. Reports from the literature provide evidences that the up-regulation of the efflux pump is liable for a decrease in β-amyloid intracellular accumulation and is an important hallmark in Alzheimer’s disease (AD). Thus, targeting β-amyloid clearance by stimulating Pgp could be a useful strategy to prevent Alzheimer’s advancement. Currently available drugs provide limited effectiveness and do not assure to cure Alzheimer’s disease completely. On the other hand, the current research is now directed towards the development of synthetic or natural based therapeutics which can delay the onset or progression of Alzheimer's disease. Since ancient time medicinal plants such as Withania somnifera, Bacopa monieri, Nerium indicum have been used to prevent neurological disorders including Alzheimer’s disease. Till today around 125 Indian medicinal plants have been screened on the basis of ethnopharmacology for their activity against neurological disorders. In this paper, we report bioactives from natural sources which show binding affinity towards the Pgp receptor using ligand based pharmacophore development, virtual screening, molecular docking and molecular dynamics simulation studies for the bioactives possessing acceptable ADME properties. These bioactives can thus be useful to treat Alzheimer’s disease.
Keywords: molecular docking